MICROBIOLOGICAL CHARACTERISTIC AND FERMENTABILITY OF KING GRASS (Pennisetum hybrid) SILAGE TREATED BY LACTIC ACID BACTERIAYEAST INOCULANTS CONSORTIUM COMBINED WITH RICE BRAN ADDITION - Sofyan, A.; Yusiati, L.M.; Widyastuti, Y.; Utomo, R. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
This research was conducted to evaluate the effect of inoculants consortium consisted ofLactobacillus plantarum (Lp) and Saccharomyces cerevisiae (Sc) and combined with rice bran additionon microbiological characteristic and fermentability of king grass (Pennisetum hybrid) silage. Effectivityof treatments was assessed by addition of inoculants (control, Lp, Lp+Sc) and level of rice bran (0, 5 and10%) which were arranged on Completely Randomized Design with Teatments Factors (3x3). Thevariables measured were total colonies of microbes (lactic acid bacteria, yeast and clostridia), total gasproduction, volatile fatty acids (VFA) and ammonia (NH3). Results showed that clostridial coloniescounted on silage treated by Lp and Lp+Sc around 37.5% and 68.7% in which lower than control.Addition of inoculants and rice bran increased fermentability of silage significantly (P<0.05), howevertreatment had no affected (P>0.05) on production of VFA and NH3. Gas production from silagefermentable fraction with inoculation of Lp (49.5 ml) and Lp+Sc (47.9 ml) higher than untreated silage(46.6 ml). It was concluded that the use of inoculants consortium consisted of L. plantarum and S.cerevisiae with rice bran addition improved fermentability and reduced clostridial colony in king grasssilage.